2022
DOI: 10.3390/ma15051768
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Manson–Coffin Curves for the Frame Material of an Unconventional Vehicle

Abstract: The submitted research paper describes the fundamental findings in terms of multiaxial fatigue of the basic material EN AW6063 and its welds for implementation in the frame design of an unconventional vehicle. It also includes a briefly-presented conceptual design of a technical solution for optimizing the functionality of a steering mechanism in a patented unconventional vehicle, designed by the authors to increase the cornering stability of a vehicle–tricycle. The most important part of this article is the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 36 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…It was specifically designed to apply both flexural and torsional loads, as well as their combination. The authors have previously published some information about this testing device in [2,7,8,19,25,26]. The research conducted on the fatigue life of the welded structural material EN AW 6063 confirmed the suitability of the chosen structural material [8].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…It was specifically designed to apply both flexural and torsional loads, as well as their combination. The authors have previously published some information about this testing device in [2,7,8,19,25,26]. The research conducted on the fatigue life of the welded structural material EN AW 6063 confirmed the suitability of the chosen structural material [8].…”
Section: Introductionmentioning
confidence: 74%
“…The authors have previously published some information about this testing device in [2,7,8,19,25,26]. The research conducted on the fatigue life of the welded structural material EN AW 6063 confirmed the suitability of the chosen structural material [8]. In this article, our objective is to emphasize additional crucial aspects that should be considered during the development of the testing device and the analysis of the results obtained from measuring the multiaxial fatigue life of the E3-kolka frame material.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations